Investing in development lessons of World Bank experience - Baum, Warren C. (Published for the World Bank [by] Oxford University Press, 1985)
This book synthesizes and makes accessible in one place some of the principal lessons learned by the World Bank in thirty-five years of financing development in its member countries. It provides guidance to developing countries in selecting, preparing, and carrying out thier whole portfolio of investment projects, regardless of the source of financing.